Recent American Art - Alley, Ronald (London : Tate Gallery, 1969)
Rothko, Mark ; Gorky, Arshile ; Pollock, Jackson ; Tobey, Mark ; Avery, Milton ; Guston, Philip ; Newman, Barnett ; Kline, Franz ; Francis, Sam ; Brooks, James ; de Kooning, Willem ; Louis, Morris ; Albers, Joseph ; Noland, Kenneth ; Poons, Larry ; Kelly, Ellsworth ; etc.
Engels
boek
Keywords: Amerika